Gastric microbial community profiling reveals a dysbiotic cancer-associated microbiota - Ferreira, RM (2018)
Objective Gastric carcinoma development is triggered by Helicobacter pylori. Chronic H. pylori infection leads to reduced acid secretion, which may allow the growth of a different gastric bacterial community. This change in the microbiome may increase aggression to the gastric mucosa and contribute to malignancy. Our aim was to evaluate the composition of the gastric microbiota in chronic gastritis and in gastric carcinoma. Design The gastric microbiota was retrospectively investigated in 54 patients with gastric carcinoma and 81 patients with chronic gastritis by 16S rRNA gene profiling, using next-generation sequencing. Differences in microbial composition of the two patient groups were assessed using linear discriminant analysis effect size. Associations between the most relevant taxa and clinical diagnosis were validated by real-time quantitative PCR. Predictive functional profiling of microbial communities was obtained with PICRUSt. Results The gastric carcinoma microbiota was characterised by reduced microbial diversity, by decreased abundance of Helicobacter and by the enrichment of other bacterial genera, mostly represented by intestinal commensals. The combination of these taxa into a microbial dysbiosis index revealed that dysbiosis has excellent capacity to discriminate between gastritis and gastric carcinoma. Analysis of the functional features of the microbiota was compatible with the presence of a nitrosating microbial community in carcinoma. The major observations were confirmed in validation cohorts from different geographic origins. Conclusions Detailed analysis of the gastric microbiota revealed for the first time that patients with gastric carcinoma exhibit a dysbiotic microbial community with genotoxic potential, which is distinct from that of patients with chronic gastritis.